Post retirement experiences of former Swedish elite athletes - Straalman, O.; Patriksson, G.; Fahlström, P. G (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Previous studies have shown that successful sport careers are often based upon the notion that athletes are living a life in harmony, and that positive adjustment to retirement is dependent on the athletes coping strategies and adjustment skills adapted during the sport career (Patriksson, 1995; Stråhlman, 2006). The aims of this study are to describe; (1) the perceptions and experiences of the road through the elite sports career, (2) experiences of the transition from elite sport to a post retirement life. Method: 36 athletes were interviewed (26 men -10 women) all with experience of top-level sport on international basis. One third of the group had finished their career before or during the 1990s and the others in the 2000s. The respondents represented various sports. The issues discussed highlight the aims of the study, and the questions where formulated to grasp the essence of the respondents` experiences. Results: The career ended for many of the respondents as a conscious planned decision, even if one third made a comeback. Only a few ended in an abrupt way. The decision to end the sport career was often a combination of reasons; lack of motivation, injury - health problems and age. The transition from elite sport went for the majority smoothly and the respondents enjoyed their retirement lives, although a small portion of them experienced problems as a direct result of their career ending. Sport still played a central role and sport related properties were important for the respondents` lives. No one regretted their elite sports career but they underlined the importance to prepare for the post retirement life. The majority of the respondents found new jobs, most sport related, and they were satisfied with their lives. Discussion: It is important not only to focus on the elite sport career, but on career support in general, especially for those with problematic adjustment. Unproblematic voluntary adjustment is often linked to the possibility to prepare in advance for retirement. Since no one reported having severe injuries that predominantly affected their post retirement life, they could put their new ambitions in other areas. Sport organisations, public authorities and individuals are all responsible for the athlete`s retirement.